Successful management of gunshot wound to the chest resulting in multiple intra-abdominal and thoracic injuries in a pediatric trauma patient: A case report and literature review. (2020) - Elkbuli, Adel; Meneses, Evander; Kinslow, Kyle; McKenney, Mark; Boneva, Dessy
Highlights: Despite hemodynamic stability on presentation, pediatric patients suffering GSW injuries should undergo extensive assessment to rule out any significant internal injuries. Renal laceration can be successfully managed with conservative observation in hemodynamically stable patients. Abstract: Introduction: Trauma remains the leading cause of mortality in the pediatric population. Penetrating thoracic injuries can result in devastating trauma to multiple organ systems. When these injuries occur, prompt diagnosis and swift treatment of internal organ injury are of utmost importance. Case presentation: A 13-year-old male presented to our Trauma Center after sustaining a gunshot wound (GSW) to the left chest. Despite his hemodynamic stability on presentation, CT scan revealed multiple injuries including splenic and renal lacerations. Exploratory laparotomy resulted in splenectomy, but no intervention was performed for the renal laceration. Instead, clinical monitoring alone was sought. Patient was discharged on hospital day 13 in stable condition. Discussion: Pediatric penetrating injuries secondary to GSWs can impact multiple organ systems. Despite hemodynamic stability on presentation, adequate staging of internal damage with CT allowed a targeted approach. In our case, non-operative management of the renal injury was implemented after hemorrhage control of his additional injuries. Failure to have done so would have inevitably complicated his overall management and made kidney salvage not feasible. Conclusion: Prompt diagnosis and treatment are required in order to prevent significant morbidity and mortality in the pediatric patient from GSW-mediated penetrating thoracic injuries. Despite hemodynamic stability on presentation, patients should be emergently assessed for severe injury, with immediate surgical management as needed. Failure to do so could lead to rapid clinical deterioration, and inability to enact other conservative measures that lead to positive outcomes.